Comparing Dimensions of Four-Strand Hamstring Tendon Grafts with Native Anterior and Posterior Cruciate Ligaments. (26th December 2016) - Yılmaz, Barış; Özdemir, Güzelali; Keskinöz, Elif N.; Tümentemur, Gamze; Gökkuş, Kemal; Demiralp, Bahtiyar
Abstract : Background . The aim of the study was to evaluate whether or not there was any incompatibility between four-strand hamstring tendons taken from the same knee and the dimensions of the ACL and PCL. Methods . 15 fresh frozen cadaver hamstrings were prepared as four-strand grafts and measurements made of the ACL and PCL circumferences in the midsection were made in the narrowest part of the midsection. The cross-section areas and diameters were calculated with geometric calculations used to measure the cross-sectional area of cylinders. Accepting that the geometric insertions were elliptical, the length, width, and area were calculated for entry areas. Results . A significant relationship at 96.2% was determined between the ACL mid and the hamstring diameter. A significant relationship at 96.7% was determined between the ACL and the hamstring mid area. A significant relationship at 96.4% was determined between the PCL mid and the hamstring diameter. A significant relationship at 95.7% was determined between the PCL and the hamstring mid area. Conclusion . For the reconstruction of ACL and PCL, it was determined that there is less incompatibility between the four-strand hamstring tendons taken from the same knee and the dimensions of the midsection PCL compared to the ACL dimensions.